Physical Activity and Health-Related Quality of Life Among Low-Income Adults in Metropolitan Kuala Lumpur - Tin, Tin Su; Azzani, Meram; Adewale, Adeoye Philip; Thangiah, Nithiah; Zainol, Rosilawati; Majid, Hazreen Abdul (Japan Epidemiological Association, 2019)
Background: The aim of this research is to assess the level of physical activity (PA) in relation to different socio-economic factors and to examine the effect of the recommended level of PA on the domains of quality of life (QoL) among residents of low-income housing in the metropolitan area of Kuala Lumpur, Malaysia. Methods: This was a cross-sectional study that included 680 respondents from community housing projects. Reported PA was assessed using the Global Physical Activity Questionnaire (GPAQ) short form version 2. The SF-12v2 was administered to assess the health-related QoL (HRQoL) among the study population. Respondents were grouped into “active” and “insufficient” groups according to reported weekly PA level. One-way analysis of variance, analysis of co-variance, and multiple linear regression were used in the analysis. Results: Overall, 17.6% (95% CI, 14.3-20.9) of the respondents did not achieve the recommended levels of PA (≥600 metabolic equivalent [MET]-minutes week -1 ). Level of achieving recommended PA was higher among younger participants, females, members belonging to nuclear families, and in self-employed participants. The group that fulfilled recommended PA levels (active) has higher levels of QoL in all domains except physical functioning. Conclusions: Almost one out of five low-income urban residents were physically inactive. In addition, individuals who attained recommended PA levels had better scores on some domains of HRQOL than those who did not. Our findings call for tailormade public health interventions to improve PA levels among the general population and particularly for low-income residents. © 2018 Tin Tin Su et al.